Sealant for organic EL display elements
By using curable resin and high-content water-absorbing filler in the sealant of the organic EL display element, the problems of decreased adhesion and insufficient moisture permeability in high temperature and high humidity environments are solved, and excellent reliability and moisture permeability are achieved.
Patent Information
- Application Number
- CN202180039446.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-22
- Filing Date
- 2021-07-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-07-19
AI Technical Summary
The adhesion of existing organic EL display elements decreases in high temperature and high humidity environments, resulting in poor reliability and moisture-proof resistance to ensure the stability of the luminescent material.
A sealant containing a curable resin and a water-absorbent filler is used. The curable resin contains a (meth)acrylic compound that does not have an isocyanate group and a blocked isocyanate group, and contains an isocyanate compound or a blocked isocyanate, and the content of the water-absorbent filler reaches 20% by weight or more.
It achieves excellent adhesion and moisture resistance in high temperature and high humidity environments, thereby improving the reliability of organic EL display elements.
Smart Images

Figure BDA0003972300020000211 
Figure BDA0003972300020000221
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing agent for an organic EL display element which is excellent in moisture permeation prevention and adhesiveness and can provide an organic EL display element with excellent reliability. Background Art
[0002] An organic electroluminescent display element (organic EL display element) has a thin film structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. Electrons are injected into the organic light-emitting material layer from one electrode, and holes are injected into the organic light-emitting material layer from the other electrode, whereby the electrons and holes are combined in the organic light-emitting material layer to emit light. Compared with liquid crystal display elements that require backlight, it has the advantages of good visibility, further thinning, and DC low voltage drive.
[0003] However, such organic EL display elements have the problem that when the organic luminescent material layer and the electrode are exposed to the outside air, the luminescent properties thereof deteriorate rapidly and the lifespan thereof becomes short. Therefore, in order to improve the stability and durability of the organic EL display element, a sealing technology for isolating the organic luminescent material layer and the electrode from moisture and oxygen in the atmosphere is indispensable in the organic EL display element.
[0004] Patent Document 1 discloses a method for sealing an organic EL display element by having an organic filling layer and a hygroscopic sealing layer (sealing wall), wherein the organic filling layer covers and seals a laminate having an organic light-emitting material layer, and the hygroscopic sealing layer covers the side of the organic filling layer. Generally, as a sealant for an organic EL display element, an in-plane sealant is used for the organic filling layer, and a peripheral sealant having a constituent component different from that of the in-plane sealant is used for the sealing wall.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-67598 Summary of the invention
[0008] Problems to be solved by the invention
[0009] An object of the present invention is to provide a sealing agent for an organic EL display element which is excellent in moisture permeation prevention and adhesiveness and can provide an organic EL display element with excellent reliability.
[0010] Means for solving problems
[0011] The present invention is a sealant for an organic EL display element, which contains a curable resin and a water-absorbing filler. The curable resin contains a (meth) acrylic compound without an isocyanate group and a blocked isocyanate group, and contains an isocyanate compound or a blocked isocyanate. The content of the water-absorbing filler is 20% by weight or more.
[0012] The present invention is described in detail below.
[0013] The present inventors have studied thinning the sealing wall for the purpose of ensuring a wider display area of the organic EL display element. However, in order to make the sealing wall thinner, the line width of the peripheral sealant is narrowed (thinned) for coating, sometimes the adhesion cannot be fully obtained, or the reliability of the obtained organic EL display element is deteriorated. In particular, in order to improve the moisture-proof property, a large amount of water-absorbent fillers are added to the peripheral sealant, and the adhesion under high temperature and high humidity environment is significantly reduced. Therefore, the present inventors have studied a solution that contains a (meth) acrylic compound that does not have an isocyanate group and a blocked isocyanate group as a curable resin, and contains an isocyanate compound or a blocked isocyanate. As a result, the obtained organic EL display element sealant has excellent moisture-proof property and adhesion, and an organic EL display element with excellent reliability can be obtained, thereby completing the present invention.
[0014] The sealing agent for an organic EL display element of the present invention contains a curable resin.
[0015] The curable resin includes a (meth)acrylic compound having no isocyanate group and no blocked isocyanate group. The curable property of the sealing agent for an organic EL display element of the present invention is excellent by including the (meth)acrylic compound having no isocyanate group and no blocked isocyanate group.
[0016] It should be noted that, in the present specification, the above-mentioned “(meth)acrylic acid” refers to acrylic acid or methacrylic acid, the above-mentioned “(meth)acrylic compound” refers to a compound having a (meth)acryloyl group, and the above-mentioned “(meth)acryloyl group” refers to an acryloyl group or a methacryloyl group.
[0017] Examples of the (meth)acrylic compound having no isocyanate group and no blocked isocyanate group include urethane (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, methylcyclohexyl (meth)acrylate, norbornyl methyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, cyclodecyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 2-hydroxyisopropyl (meth)acrylate. Among them, from the viewpoint of further improving the adhesion and moisture permeability of the obtained sealant for organic EL display elements, and improving the compatibility with the polyolefin described later, the above-mentioned (meth) acrylic compound without isocyanate group and blocked isocyanate group preferably includes a (meth) acrylic compound with an alicyclic skeleton. In addition, from the viewpoint of further improving the adhesion (especially the adhesion under high temperature and high humidity environment) of the obtained sealant for organic EL display elements, the above-mentioned (meth) acrylic compound without isocyanate group and blocked isocyanate group preferably includes a multifunctional (meth) acrylic compound.
[0018] It should be noted that, in this specification, the above-mentioned "(meth)acrylate" refers to acrylate or methacrylate, and the above-mentioned "urethane (meth)acrylate" refers to a compound having a urethane bond and a (meth)acryloyl group. In addition, a "multifunctional (meth)acrylic compound" refers to a compound having two or more (meth)acryloyl groups in one molecule.
[0019] The preferred lower limit of the content of the (meth) acrylic compound without an isocyanate group and a blocked isocyanate group in 100 parts by weight of the curable resin as a whole is 0.01 parts by weight, and the preferred upper limit is 99.99 parts by weight. By making the content of the (meth) acrylic compound without an isocyanate group and a blocked isocyanate group within this range, the adhesiveness and storage stability of the sealant for the obtained organic EL display element are more excellent. The more preferred lower limit of the content of the (meth) acrylic compound without an isocyanate group and a blocked isocyanate group is 0.1 parts by weight, the further preferred lower limit is 10 parts by weight, the further preferred lower limit is 20 parts by weight, and the particularly preferred lower limit is 80 parts by weight.
[0020] The curable resin contains an isocyanate compound or a blocked isocyanate. By containing the isocyanate compound or the blocked isocyanate and making the content ratio of the water-absorbing filler described later within the range described later, the sealant for the organic EL display element of the present invention has excellent adhesion (especially adhesion in a high temperature and high humidity environment), and the obtained organic EL display element has excellent reliability.
[0021] The isocyanate compound or the blocked isocyanate may or may not have a (meth)acryloyl group. In particular, from the viewpoint of further improving the adhesion (particularly adhesion in a high temperature and high humidity environment) and storage stability of the obtained sealant for organic EL display elements, it is preferred to have a (meth)acryloyl group.
[0022] Examples of the isocyanate compound having a (meth)acryloyl group include 2-(meth)acryloyloxyethyl isocyanate and 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate. Among them, 2-(meth)acryloyloxyethyl isocyanate is preferred.
[0023] Examples of the blocked isocyanate having a (meth)acryloyl group include 2-((3,5-dimethylpyrazolyl)carbonylamino)ethyl (meth)acrylate, 2-(O-(1'-methylpropyleneamino)carboxylamino)ethyl (meth)acrylate, and 2-(O-(1'-methylpropyleneamino)carboxylamino) (meth)acrylate. Among them, 2-((3,5-dimethylpyrazolyl)carbonylamino)ethyl (meth)acrylate is preferred.
[0024] Examples of the compound not having a (meth)acryloyl group in the isocyanate compound or the blocked isocyanate include aromatic isocyanates, aliphatic isocyanates having an aromatic ring, aliphatic isocyanates not having an aromatic ring, and alicyclic isocyanates.
[0025] Examples of the aromatic isocyanate include tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, a polymer of methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate.
[0026] Examples of the aliphatic isocyanate having an aromatic ring include α,α,α′,α′-tetramethylxylylene diisocyanate and the like.
[0027] Examples of the aliphatic isocyanate having no aromatic ring include methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate.
[0028] Examples of the alicyclic isocyanate include cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), and isopropyl dicyclohexyl diisocyanate.
[0029] Among them, methylene diphenyl diisocyanate and polymers of methylene diphenyl diisocyanate are preferred from the viewpoint of adhesiveness.
[0030] As the isocyanate compound or the blocked isocyanate, the isocyanate compound is preferred from the viewpoint of adhesiveness, and the blocked isocyanate is preferred from the viewpoint of storage stability.
[0031] The preferred lower limit of the content of the above-mentioned isocyanate compound or the above-mentioned blocked isocyanate in 100 parts by weight of the above-mentioned curable resin as a whole is 0.05 parts by weight, and the preferred upper limit is 8 parts by weight. By making the content of the above-mentioned isocyanate compound or the above-mentioned blocked isocyanate within this range, the adhesion (especially adhesion under high temperature and high humidity environment) and storage stability of the obtained organic EL display element sealant become more excellent. The more preferred lower limit of the content of the above-mentioned isocyanate compound or the above-mentioned blocked isocyanate is 0.1 parts by weight, and the more preferred upper limit is 5 parts by weight.
[0032] The curable resin may contain other curable resins in addition to the (meth)acrylic compound having no isocyanate group and no blocked isocyanate group, and the isocyanate compound or the blocked isocyanate.
[0033] Examples of the other curable resins include epoxy compounds, oxetane compounds, and urethane compounds having no (meth)acryloyl group.
[0034] As said epoxy compound, a glycidyl ether compound, an alicyclic epoxy compound, etc. are mentioned, for example.
[0035] Examples of the glycidyl ether compound include diethylene glycol diglycidyl ether and the like.
[0036] Examples of the alicyclic epoxy compound include 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate and 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol.
[0037] Examples of the oxetane compound include 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, di[2-(3-oxetanyl)butyl]ether, and 3-ethyl-3-hydroxymethyloxetane.
[0038] As said urethane compound which does not have a (meth)acryloyl group, the reaction product of an isocyanate compound and arbitrary polyol compounds etc. are mentioned, for example.
[0039] As said isocyanate compound, a tolylene diisocyanate compound, a diphenylmethane diisocyanate compound, etc. are mentioned, for example.
[0040] Examples of the tolylene diisocyanate compound include 2,4-tolylene diisocyanate (2,4-TDI), 2,6-tolylene diisocyanate, and a mixture thereof.
[0041] As said diphenylmethane diisocyanate compound, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, or a mixture thereof etc. are mentioned, for example.
[0042] When the curable resin contains blocked isocyanate, it is preferred to further contain an amine compound. By containing an amine compound, the blocked isocyanate can be gradually converted into isocyanate, and the storage stability and adhesiveness can be improved at the same time.
[0043] Examples of the amine compound include 1,4-diazabicyclo[2.2.2]octane and the like.
[0044] The amount of the amine compound added is preferably 1 part by weight or more and 20 parts by weight or less relative to 100 parts by weight of the blocked isocyanate.
[0045] The sealing agent for an organic EL display element of the present invention contains a water-absorbing filler. By containing the water-absorbing filler, the sealing agent for an organic EL display element of the present invention has excellent moisture permeation prevention property.
[0046] Examples of the water-absorbing filler include oxides of alkaline earth metals, magnesium oxide, and molecular sieves.
[0047] Examples of the alkaline earth metal oxides include calcium oxide, strontium oxide, and barium oxide.
[0048] Among them, from the viewpoint of water absorption, oxides of alkaline earth metals are preferred, and calcium oxide is more preferred.
[0049] These water-absorbing fillers may be used alone or in combination of two or more.
[0050] The lower limit of the content ratio of the above-mentioned water-absorbing filler in the sealant for organic EL display element of the present invention is 20% by weight. By making the content ratio of the above-mentioned water-absorbing filler more than 20% by weight, the sealant for organic EL display element of the present invention has excellent moisture permeability. In addition, the sealant for organic EL display element of the present invention contains the above-mentioned isocyanate compound or the above-mentioned blocked isocyanate, so that even if a large amount of the above-mentioned water-absorbing filler is added, the adhesion (especially the adhesion under high temperature and high humidity environment) is also excellent, and the reliability of the obtained organic EL display element is excellent. The preferred lower limit of the content ratio of the above-mentioned water-absorbing filler is 30% by weight, and the more preferred lower limit is 40% by weight.
[0051] From the viewpoint of coating properties and the like, the upper limit of the content of the water-absorbing filler is preferably 70% by weight, and the more preferably 60% by weight.
[0052] The sealing agent for an organic EL display element of the present invention may contain other fillers in addition to the water-absorbing filler as long as the object of the present invention is not impaired.
[0053] As the other fillers, inorganic fillers and organic fillers can be used.
[0054] Examples of the inorganic filler include silica, talc, and alumina.
[0055] Examples of the organic filler include polyester microparticles, polyurethane microparticles, vinyl polymer microparticles, acrylic polymer microparticles, etc. Among them, talc is preferred.
[0056] The sealing agent for an organic EL display element of the present invention preferably contains a polyolefin.
[0057] By containing the above-mentioned polyolefin, the sealing agent for organic EL display elements of the present invention has more excellent moisture permeation prevention property.
[0058] From the viewpoint of further improving the moisture permeation barrier property, the polyolefin preferably contains at least one selected from polyisobutylene, polybutene, and polybutadiene, and more preferably contains polyisobutylene.
[0059] The above-mentioned polyolefins may be used alone or in combination of two or more.
[0060] The preferred lower limit of the weight average molecular weight of the polyolefin is 10,000, and the preferred upper limit is 400,000. By making the weight average molecular weight of the polyolefin within this range, the coating property, adhesion and moisture permeability of the obtained sealant for organic EL display element are more excellent. The more preferred lower limit of the weight average molecular weight of the polyolefin is 20,000, and the more preferred upper limit is 70,000.
[0061] It should be noted that, in this specification, the above-mentioned "weight average molecular weight" is a value obtained by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent and converted to polystyrene. As a column used when measuring the weight average molecular weight based on polystyrene conversion by GPC, for example, Shodex LF-804 (Showa Denko Co., Ltd.) etc. can be cited.
[0062] The preferred lower limit of the content of the above-mentioned polyolefin in the total of 100 parts by weight of the above-mentioned curable resin and the above-mentioned polyolefin is 10 parts by weight, and the preferred upper limit is 80 parts by weight. By making the content of the above-mentioned polyolefin more than 10 parts by weight, the moisture permeability of the obtained organic EL display element sealant is more excellent. By making the content of the above-mentioned polyolefin less than 80 parts by weight, the coating and adhesion of the obtained organic EL display element sealant are more excellent. The more preferred lower limit of the content of the above-mentioned polyolefin is 20 parts by weight, and the more preferred upper limit is 60 parts by weight.
[0063] The sealing agent for an organic EL display element of the present invention may contain a tackifier resin for the purpose of further improving adhesiveness or the like.
[0064] Examples of the tackifier resin include terpene resins, modified terpene resins, coumarone resins, indene resins, and petroleum resins.
[0065] Examples of the modified terpene resin include hydrogenated terpene resins, terpene-phenol copolymer resins, and aromatic modified terpene resins.
[0066] Examples of the petroleum resin include aliphatic petroleum resins, hydrogenated alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic copolymerized petroleum resins, alicyclic petroleum resins, dicyclopentadiene petroleum resins, and hydrogenated products thereof.
[0067] Among them, as the above-mentioned tackifying resin, from the viewpoints of adhesion, moisture permeation resistance, compatibility, etc. of the sealant for organic EL display elements, terpene resins, aromatic modified terpene resins, terpene-phenol copolymer resins, hydrogenated alicyclic petroleum resins, aromatic petroleum resins, aliphatic aromatic copolymer petroleum resins, alicyclic petroleum resins are preferred, alicyclic petroleum resins are more preferred, alicyclic saturated hydrocarbon resins, alicyclic unsaturated hydrocarbon resins are further preferred, and saturated hydrocarbon resins containing cyclohexyl rings and dicyclopentadiene-modified hydrocarbon resins are particularly preferred.
[0068] These tackifier resins may be used alone or in combination of two or more.
[0069] Relative to 100 parts by weight of the curable resin (the total of the curable resin and the polyolefin in the case of containing the polyolefin), the preferred lower limit of the content of the tackifying resin is 0.01 parts by weight, and the preferred upper limit is 100 parts by weight. By making the content of the tackifying resin within this range, the effect of improving adhesion while maintaining moisture permeability can be further exerted. The more preferred lower limit of the content of the tackifying resin is 0.2 parts by weight, and the more preferred upper limit is 20 parts by weight.
[0070] The sealing agent for an organic EL display element of the present invention preferably contains a polymerization initiator.
[0071] As the polymerization initiator, a radical polymerization initiator or a cationic polymerization initiator can be used, among which a radical polymerization initiator is preferred.
[0072] Examples of the radical polymerization initiator include a photoradical polymerization initiator and a thermal radical polymerization initiator.
[0073] Examples of the photoradical polymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds.
[0074] Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 1,2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinophenyl)phenyl)-1-butanone, 2,2-dimethoxy-2-phenylacetophenone, bis(2,4,6-trimethylbenzoyl)phenyl phosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propane-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyl oxime), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, etc.
[0075] As said thermal radical polymerization initiator, the thermal radical polymerization initiator containing an azo compound, an organic peroxide, etc. is mentioned, for example.
[0076] Examples of the azo compound include 2,2′-azobis(2,4-dimethylvaleronitrile) and azobisisobutyronitrile.
[0077] Examples of the organic peroxide include benzoyl peroxide, ketone peroxide, peroxyketal, hydrogen peroxide, dialkyl peroxide, peroxyester, diacyl peroxide, and peroxydicarbonate.
[0078] Examples of commercially available products of the thermal radical polymerization initiator include VPE-0201, VPE-0401, VPE-0601, VPS-0501, VPS-1001, and V-501 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0079] Examples of the cationic polymerization initiator include a photocationic polymerization initiator and a thermal cationic polymerization initiator.
[0080] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid by light irradiation, and may be an ionic photoacid generating type or a nonionic photoacid generating type.
[0081] Examples of the anion portion of the ionic photoacid generating type photocationic polymerization initiator include BF 4 - PF 6 - , SbF 6 - or (BX 4 ) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups) and the like.
[0082] Examples of the ionic photoacid generating type photocationic polymerization initiator include aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salts having the anion moiety.
[0083] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, and triphenylsulfonium tetrakis(pentafluorophenyl)borate. Phenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, triarylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, tris(4-(4-acetylphenyl)phenylthio)sulfonium tetrakis(pentafluorophenyl)borate, and the like.
[0084] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate, and the like.
[0085] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.
[0086] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, and the like.
[0087] Examples of the above-mentioned (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.
[0088] Examples of the nonionic photoacid-generating photocationic polymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidesulfonic acid esters.
[0089] Examples of commercially available photocationic polymerization initiators include photocationic polymerization initiators manufactured by MIDORI KAGAKU, photocationic polymerization initiators manufactured by Union Carbide, photocationic polymerization initiators manufactured by ADEKA, photocationic polymerization initiators manufactured by 3M, photocationic polymerization initiators manufactured by BASF, and photocationic polymerization initiators manufactured by Rhodia.
[0090] As the photocationic polymerization initiator manufactured by MIDORI KAGAKU CO., LTD., DTS-200 etc. are mentioned, for example.
[0091] As the photocationic polymerization initiator manufactured by the Union Carbide Co., Ltd., for example, UVI6990, UVI6974, etc. may be mentioned.
[0092] As said ADEKA photocationic polymerization initiator, SP-150, SP-170 etc. are mentioned, for example.
[0093] Examples of the photocationic polymerization initiator manufactured by 3M include FC-508 and FC-512.
[0094] As said BASF company's photocationic polymerization initiator, IRGACURE261, IRGACURE290 etc. are mentioned, for example.
[0095] As the photocationic polymerization initiator manufactured by the Rhodia company, for example, PI2074 etc. can be mentioned.
[0096] Examples of the thermal cationic polymerization initiator include an anion portion composed of BF 4 - PF 6 - , SbF 6 - or (BX 4 ) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups) sulfonium salts, phosphonium salts, ammonium salts, etc. Among them, sulfonium salts and ammonium salts are preferred.
[0097] Examples of the sulfonium salt include triphenylsulfonium tetrafluoroborate and triphenylsulfonium hexafluoroantimonate.
[0098] Examples of the phosphonium salt include ethyltriphenylphosphonium hexafluoroantimonate and tetrabutylphosphonium hexafluoroantimonate.
[0099] Examples of the ammonium salt include dimethylphenyl(4-methoxybenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methoxybenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methylbenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium hexafluorophosphate, and methylphenyldibenzylammonium hexafluorophosphate. hexafluoroantimonate, methylphenyldibenzylammonium tetra(pentafluorophenyl)borate, phenyltribenzylammonium tetra(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetra(pentafluorophenyl)borate, N,N-dimethyl-N-benzylanilinium hexafluoroantimonate, N,N-diethyl-N-benzylanilinium tetrafluoroborate, N,N-dimethyl-N-benzylpyridinium hexafluoroantimonate, N,N-diethyl-N-benzylpyridinium trifluoromethanesulfonic acid, etc.
[0100] As a commercial item among the said thermal cationic polymerization initiators, the thermal cationic polymerization initiator manufactured by Sanshin Chemical Industry Co., Ltd. and the thermal cationic polymerization initiator manufactured by King Industries, Ltd. etc. are mentioned, for example.
[0101] Examples of the thermal cationic polymerization initiator manufactured by Sanshin Chemical Industries, Ltd. include San-Aid SI-60, San-Aid SI-80, San-Aid SI-B3, San-Aid SI-B3A, and San-Aid SI-B4.
[0102] Examples of the thermal cationic polymerization initiator manufactured by King Industries include CXC-1612 and CXC-1821.
[0103] Relative to 100 parts by weight of the curable resin (the sum of the curable resin and the polyolefin in the case of containing the polyolefin), the preferred lower limit of the content of the polymerization initiator is 0.05 parts by weight, and the preferred upper limit is 10 parts by weight. By making the content of the polymerization initiator more than 0.05 parts by weight, the curability of the obtained organic EL display element sealant is more excellent. By making the content of the polymerization initiator less than 10 parts by weight, the curing reaction of the obtained organic EL display element sealant will not become too fast, the workability is better, and the cured product can be made more uniform. The more preferred lower limit of the content of the polymerization initiator is 1 part by weight, and the more preferred upper limit is 3 parts by weight.
[0104] The sealing agent for an organic EL display element of the present invention may contain a sensitizer. The sensitizer has a function of further improving the polymerization initiation efficiency of the polymerization initiator and further promoting the curing reaction of the sealing agent for an organic EL display element of the present invention.
[0105] Examples of the sensitizer include anthracene compounds, thioxanthone compounds, 2,2-dimethoxy-1,2-diphenylethane-1-one, benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4′-bis(dimethylamino)benzophenone, and 4-benzoyl-4′-methyldiphenyl sulfide.
[0106] Examples of the anthracene-based compound include 9,10-dibutoxyanthracene and the like.
[0107] Examples of the thioxanthone-based compound include 2,4-diethylthioxanthone and the like.
[0108] These sensitizers may be used alone or in combination of two or more.
[0109] The preferred lower limit of the content of the sensitizer is 0.05 parts by weight, and the preferred upper limit is 3 parts by weight relative to 100 parts by weight of the curable resin (the total of the curable resin and the polyolefin when the polyolefin is contained). By making the content of the sensitizer more than 0.05 parts by weight, the sensitization effect is further exerted. By making the content of the sensitizer less than 3 parts by weight, it will not cause the absorption to become too large, and light can be transmitted to the deep part. The more preferred lower limit of the content of the sensitizer is 0.1 parts by weight, and the more preferred upper limit is 1 part by weight.
[0110] The sealing agent for an organic EL display element of the present invention may contain a thermosetting agent.
[0111] Examples of the thermosetting agent include hydrazide compounds, imidazole derivatives, acid anhydrides, dicyandiamide, guanidine derivatives, modified aliphatic polyamines, and addition products of various amines and epoxy resins.
[0112] Examples of the hydrazide compound include 1,3-bis(hydrazinocarbonylethyl)-5-isopropylhydantoin, sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide.
[0113] Examples of the imidazole derivatives include 1-cyanoethyl-2-phenylimidazole, N-(2-(2-methyl-1-imidazolyl)ethyl)urea, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, N,N'-bis(2-methyl-1-imidazolylethyl)urea, N,N'-(2-methyl-1-imidazolylethyl)-adipic acid diamide, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2-phenyl-4,5-dihydroxymethylimidazole.
[0114] Examples of the acid anhydride include tetrahydrophthalic anhydride and ethylene glycol bis(anhydrotrimellitate).
[0115] These thermosetting agents may be used alone or in combination of two or more.
[0116] Examples of commercially available products of the thermosetting agent include SDH (manufactured by Nippon Finechem Co., Ltd.), ADH (manufactured by Otsuka Chemical Co., Ltd.), Amicure VDH, Amicure VDH-J, and Amicure UDH (all manufactured by Ajinomoto Fine-Techno Co., Ltd.).
[0117] Relative to 100 parts by weight of the curable resin (the sum of the curable resin and the polyolefin in the case of containing the polyolefin), the preferred lower limit of the content of the thermosetting agent is 0.01 parts by weight, and the preferred upper limit is 10 parts by weight. By making the content of the thermosetting agent more than 0.01 parts by weight, the thermosetting property of the obtained organic EL display element sealant is more excellent. By making the content of the thermosetting agent less than 10 parts by weight, the storage stability of the obtained organic EL display element sealant is more excellent. The more preferred lower limit of the content of the thermosetting agent is 0.5 parts by weight, the more preferred upper limit is 5 parts by weight, the further preferred lower limit is 1 part by weight, and the further preferred upper limit is 3 parts by weight.
[0118] The sealing agent for an organic EL display element of the present invention may contain a stabilizer. By containing the stabilizer, the sealing agent for an organic EL display element of the present invention has more excellent storage stability.
[0119] Examples of the stabilizer include aromatic amine compounds and 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (Okisil).
[0120] Examples of the aromatic amine compound include benzylamine and aminophenol-type epoxy resins.
[0121] Among them, aromatic amine compounds are preferred, and benzylamine is more preferred.
[0122] These stabilizers may be used alone or in combination of two or more.
[0123] The preferred lower limit of the content of the stabilizer is 0.001 parts by weight and the preferred upper limit is 2 parts by weight relative to 100 parts by weight of the curable resin (the total of the curable resin and the polyolefin when the polyolefin is contained). By making the content of the stabilizer within this range, the obtained sealant for organic EL display elements has better storage stability while maintaining excellent curability. The more preferred lower limit of the content of the stabilizer is 0.005 parts by weight and the more preferred upper limit is 1 part by weight.
[0124] The sealing agent for an organic EL display element of the present invention may contain a silane coupling agent. The silane coupling agent has a function of improving the adhesion between the sealing agent for an organic EL display element of the present invention and a substrate or the like.
[0125] Examples of the silane coupling agent include 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-isocyanatepropyltrimethoxysilane.
[0126] These silane coupling agents may be used alone or in combination of two or more.
[0127] The preferred lower limit of the content of the silane coupling agent is 0.1 parts by weight, and the preferred upper limit is 10 parts by weight, relative to 100 parts by weight of the curable resin (the total of the curable resin and the polyolefin when the polyolefin is contained). By making the content of the silane coupling agent within this range, the effect of preventing the excess silane coupling agent from seeping out and improving the adhesion of the obtained sealant for organic EL display elements is more excellent. The more preferred lower limit of the content of the silane coupling agent is 0.5 parts by weight, and the more preferred upper limit is 5 parts by weight.
[0128] The sealing agent for organic EL display elements of the present invention may contain a surface modifier within a range that does not hinder the purpose of the present invention. By containing the surface modifier, the flatness of the coating film of the sealing agent for organic EL display elements of the present invention can be improved.
[0129] Examples of the surface modifier include surfactants and leveling agents.
[0130] Examples of the surface modifier include silicone-based, acrylic-based, and fluorine-based surface modifiers.
[0131] Examples of commercially available products of the surface modifier include surface modifiers manufactured by BYK Chemie Japan, surface modifiers manufactured by Kusumoto Chemicals Co., Ltd., and surface modifiers manufactured by AGC Seimi Chemical Co., Ltd.
[0132] Examples of the surface modifier manufactured by BYK Chemie Japan include BYK-300, BYK-302, and BYK-331.
[0133] Examples of the surface modifier manufactured by Kusumoto Chemicals Co., Ltd. include UVX-272.
[0134] Examples of the surface modifier manufactured by AGC SEIMI CHEMICAL include SURFLON S-611.
[0135] The sealing agent for an organic EL display element of the present invention may contain a compound and / or an ion exchange resin that reacts with an acid generated in the sealing agent for an organic EL display element within a range not hindering the purpose of the present invention.
[0136] Examples of the compound that reacts with the generated acid include substances that neutralize with the acid, such as carbonates or hydrogen carbonates of alkali metals, or carbonates or hydrogen carbonates of alkaline earth metals, etc. Specifically, for example, calcium carbonate, calcium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, etc. can be used.
[0137] As the ion exchange resin, any of a cation exchange type, anion exchange type, and amphoteric ion exchange type can be used, and a cation exchange type or amphoteric ion exchange type capable of adsorbing chloride ions is particularly preferred.
[0138] The sealing agent for an organic EL display element of the present invention may contain various known additives such as a curing retarder, a reinforcing agent, a softener, a plasticizer, a viscosity modifier, an ultraviolet absorber, and an antioxidant as needed within a range not hindering the purpose of the present invention.
[0139] From the viewpoint of further suppressing the generation of outgassing, the sealing agent for an organic EL display element of the present invention preferably contains no solvent. The sealing agent for an organic EL display element of the present invention can achieve excellent coating properties even if it contains no solvent.
[0140] It should be noted that, in the present specification, “containing no solvent” means that the content of the solvent is less than 1000 ppm.
[0141] Examples of a method for producing the sealant for an organic EL display element of the present invention include a method of mixing polyolefin, curable resin, water-absorbing filler, polymerization initiator and / or thermosetting agent, and additives such as a silane coupling agent added as needed using a mixer.
[0142] Examples of the mixer include a homodisperser, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mill.
[0143] The preferred upper limit of the viscosity of the sealant for organic EL display elements of the present invention measured using an E-type viscometer at 25°C and 2.5 rpm is 1000 Pa·s. By setting the viscosity to 1000 Pa·s or less, the sealant for organic EL display elements obtained has excellent coating properties. The more preferred upper limit of the viscosity is 500 Pa·s.
[0144] In addition, the preferred lower limit of the viscosity is not particularly limited, but the actual lower limit is 100 Pa·s.
[0145] The lower limit of the adhesive strength of the cured product of the organic EL display element sealant of the present invention to glass after being stored in an environment of 85° C. and 85% RH for 500 hours is preferably 0.8 kgf / cm 2After the cured product was stored at 85°C and 85% RH for 500 hours, its adhesion to glass was 0.8 kgf / cm 2 The above-mentioned organic EL display element sealant of the present invention can be suitably used as a peripheral sealant for organic EL display elements. The lower limit of the adhesive force of the cured product to glass after being stored at 85°C and 85% RH for 500 hours is more preferably 1.2 kgf / cm 2 .
[0146] The upper limit of the adhesive force of the cured product to glass after being stored at 85°C and 85% RH for 500 hours is not particularly limited, but the upper limit is substantially 3.0 kgf / cm 2 .
[0147] The cured product of the sealant for organic EL display element of the present invention is preferably used as a sealing wall surrounding the peripheral portion of the organic EL display element. That is, the sealant for organic EL display element of the present invention is preferably used as a peripheral sealant for organic EL display element for forming a sealing wall around a laminate having an organic light-emitting material layer. The peripheral sealant for organic EL display element is usually used in combination with an in-plane sealant for organic EL display element covering the laminate.
[0148] From the viewpoint of ensuring that the display area of the obtained organic EL display element is relatively wide, the thickness of the sealing wall formed by the cured product of the organic EL display element sealant of the present invention is preferably 5 mm or less, more preferably 3 mm or less, and further preferably 2 mm or less in the line width direction. The sealant for the organic EL display element of the present invention has excellent moisture permeability, adhesion and reliability, so the sealing wall can be made to have a thickness below the above upper limit. The lower limit of the thickness of the sealing wall in the line width direction is not particularly limited, for example, 0.5 mm.
[0149] Effects of the Invention
[0150] According to the present invention, it is possible to provide a sealing agent for an organic EL display element which is excellent in moisture permeation prevention and adhesiveness and can provide an organic EL display element with excellent reliability. DETAILED DESCRIPTION
[0151] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0152] (Examples 1 to 9, Comparative Examples 1 and 2)
[0153] The materials were stirred and mixed at 2000 rpm for 3 minutes using a stirring mixer according to the mixing ratios listed in Tables 1 and 2 to prepare sealing agents for organic EL display elements of Examples 1 to 9 and Comparative Examples 1 and 2. AR-250 (manufactured by THINKY) was used as the stirring mixer.
[0154] In addition, as calcium oxide in Tables 1 and 2, the calcium oxide used was the one obtained by batch-crushing using a ball mill (manufactured by Nippon To Science Co., Ltd., “ANZ-53D”) so as to have a particle size of 10 μm or less.
[0155] <Evaluation>
[0156] The following evaluations were performed on the sealing agents for organic EL display elements obtained in Examples and Comparative Examples.
[0157] (1) Viscosity and storage stability
[0158] The initial viscosity of each of the sealing agents for organic EL display elements obtained in Examples and Comparative Examples was measured at 25° C. immediately after production using an E-type viscometer.
[0159] In addition, each sealant for an organic EL display element was frozen and stored for 2 weeks after production, and then thawed, and the viscosity at 25°C was measured, and (viscosity after frozen storage for 2 weeks) / (initial viscosity) was taken as the viscosity change rate. The case where the viscosity change rate was less than 1.1 was set as "◎", the case where it was 1.1 or more and less than 1.3 was set as "○", the case where it was 1.3 or more and less than 1.5 was set as "△", and the case where it was 1.5 or more was set as "×", and the storage stability was evaluated.
[0160] As the E-type viscometer, VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) was used.
[0161] (2) Adhesion
[0162] With respect to 10g of each sealant for organic EL display elements obtained in the examples and comparative examples, 0.03g of spacer particles with a diameter of 10μm was added and uniformly dispersed using a stirring mixer. Micropearl SP-210 (manufactured by Sekisui Chemical Co., Ltd.) was used as the above-mentioned spacer particles, and ARV-310 (manufactured by THINKY Co., Ltd.) was used as the above-mentioned stirring mixer. After the sealant for organic EL display elements dispersed with spacer particles was applied to the center portion of glass substrate A, glass substrate B was cross-attached in a cross-like manner and pressurized to make the thickness uniform. The amount of the sealant for organic EL display elements applied was adjusted so that the sealant for organic EL display elements after being pressurized and having a uniform thickness became a circle with a diameter of 5.0 to 7.0mm. The above-mentioned glass substrates A and B were obtained by cleaning the surface of glass with a length of 60mm, a width of 30mm, and a thickness of 5mm with acetone and then drying it. Next, ultraviolet rays with a wavelength of 365nm were irradiated at 3000mJ / cm 2 The sealant for the organic EL display element was cured, thereby bonding the glass substrate A and the glass substrate B to obtain a test piece for initial adhesion evaluation. In addition, after bonding the glass substrate A and the glass substrate B in the same manner as the test piece for initial adhesion evaluation, the test piece was exposed to high temperature and high humidity conditions of 85°C and 85%RH for 500 hours to obtain a test piece for adhesion evaluation after exposure to a high temperature and high humidity environment.
[0163] For each test piece, the glass substrate B was arranged downward, the two ends of the glass substrate A were fixed from below, and the two ends of the glass substrate B were compressed from above by a precision universal testing machine at 23°C and a speed of 5mm / min, thereby measuring the adhesive force between the glass substrate A and the glass substrate B. The compressed part was centered at a position 7.25mm from the two ends of the glass substrate B, and was set to a range of 20mm in length and 5mm in width. As the above-mentioned precision universal testing machine, Autograph AG-Xplus (made by Shimadzu Corporation) was used.
[0164] The adhesive strength was set to the value obtained by dividing the maximum load from the start of compression to the complete separation of the glass substrate A and the glass substrate B by the area of the sealant for organic EL display elements of the test piece using a precision universal testing machine. 2 The above situation is marked as "◎", and the adhesive force is less than 2.0kgf / cm 2 And 1.5kgf / cm 2 The above cases are marked as "○", and the adhesive force is less than 1.5 kgf / cm 2 And 0.8kgf / cm 2 The above situation is set as "△", and the adhesive force is less than 0.8kgf / cm 2The cases with "×" were rated as "×", and the initial adhesion and the adhesion after exposure to a high temperature and high humidity environment were evaluated.
[0165] (3) Moisture-proof
[0166] The following Ca-TEST was performed on each of the sealing agents for organic EL display elements obtained in Examples and Comparative Examples.
[0167] First, 0.03 g of spacer particles with a diameter of 10 μm were added to 10 g of each sealant for organic EL display elements obtained in the examples and comparative examples, and the spacer particles were uniformly dispersed using a stirring mixer. Micropearl SP-210 (manufactured by Sekisui Chemical Co., Ltd.) was used as the spacer particles, and ARV-310 (manufactured by THINKY Co., Ltd.) was used as the stirring mixer. Next, the organic EL display element sealant in which the spacer particles were dispersed was applied to the surface of the glass substrate.
[0168] Next, a mask having a plurality of 2 mm×2 mm openings was placed on another glass substrate of 30 mm×30 mm size, and Ca was deposited using a vacuum deposition apparatus. The deposition conditions were as follows: the pressure inside the deposition chamber of the vacuum deposition apparatus was reduced to 2×10 -3 Pa, Ca The deposition rate of the film The glass substrate on which Ca was vapor-deposited was moved into a glove box controlled at a dew point (above -60°C), and the glass substrate on which the surface of the organic EL display element sealant was coated was bonded to the glass substrate on which Ca was vapor-deposited so that the organic EL display element sealant was on the Ca vapor-deposited pattern. After pressurization to make the thickness of the organic EL display element sealant layer uniform, the glass substrate was irradiated with 3000 mJ / cm using a UV-LED irradiation device. 2 The organic EL display element sealant is cured by ultraviolet light with a wavelength of 365nm to produce a Ca-TEST substrate.
[0169] The obtained Ca-TEST substrate was exposed to high temperature and high humidity conditions of 85° C. and 85% RH, and the penetration distance of water from the end surface of the glass substrate to the layer containing the cured product of the organic EL display element sealant was observed based on the disappearance of Ca.
[0170] As a result, the moisture penetration distance when the exposure time to high temperature and high humidity conditions was 900 hours was set as "◎" when it was less than 1.8 mm, "○" when it was 1.8 mm or more and less than 2.1 mm, "△" when it was 2.1 mm or more and less than 2.4 mm, and "×" when it was 2.4 mm or more to evaluate the moisture permeability prevention.
[0171] [Table 1]
[0172]
[0173] [Table 2]
[0174]
[0175] Industrial Applicability
[0176] According to the present invention, it is possible to provide a sealing agent for an organic EL display element which is excellent in moisture permeation prevention and adhesiveness and can provide an organic EL display element with excellent reliability.
Claims
1. A sealant for an organic EL display element, characterized in that: Contains curable resin and water-absorbing filler. The curable resin includes a (meth)acrylic compound having no isocyanate group and no blocked isocyanate group, and includes an isocyanate compound or a blocked isocyanate. The isocyanate compound or the blocked isocyanate has a (meth)acryloyl group, The content of the water-absorbing filler is 20% by weight or more.
2. The sealing agent for an organic EL display element according to claim 1, wherein The (meth)acrylic compound having no isocyanate group and no blocked isocyanate group includes a (meth)acrylic compound having an alicyclic skeleton.
3. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The (meth)acrylic compound having no isocyanate group and no blocked isocyanate group includes a polyfunctional (meth)acrylic compound.
4. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The water-absorbing filler comprises calcium oxide. 5 . The sealing agent for an organic EL display element according to claim 1 , further comprising a polyolefin.
6. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The viscosity measured using an E-type viscometer at 25° C. and 2.5 rpm was 1000 Pa·s or less.
7. The sealing agent for an organic EL display element according to claim 1 or 2, wherein After being stored at 85°C and 85% RH for 500 hours, the adhesion of the cured product to glass is 0.8 kgf / cm 2 above. 8 . The sealant for an organic EL display element according to claim 1 , which is used as a peripheral sealant for an organic EL display element for forming a sealing wall around a laminate having an organic light-emitting material layer.
Citation Information
Patent Citations
Organic electroluminescent panel and method for manufacturing the same
JP2014067598A
Photocurable adhesive film for organic electronic device seal, organic electronic device, and method for sealing same
CN103959501A
Organic electronic device
WO2019124923A1